Strengthening pathogen genomic surveillance: the way forward - Yee, Yu Choo; Zakaria, Zunita; Mat Isa, Nurulfiza; Yong, Ang Geik (Malaysian University Research Officer Society, 2024)
Next-generation sequencing (NGS) technologies were instrumental in the identification and evolutional tracking of SARS-CoV-2 during the COVID-19 pandemic. The mass generation of SARS-CoV-2 genomic sequences led to timely identification of emerging variants, allowing for more informed decision making in combating the disease and in monitoring of vaccines efficacy. Hence, NGS facilities were strengthened around the world as reflected by the scale of the genomic surveillance of SARS-CoV-2 in which more than 17 million of SARS-CoV-2 genomic sequences have been deposited in the EpiCoV database of Global Initiative on Sharing All Influenza Data. Although NGS facilities are now accessible in many countries, the adaptation of the NGS technologies for genomic surveillance of other pathogens may pose a challenge. NGS is a revolutionary genomic surveillance tool for bacteria, viruses, fungi and protozoa but the integration of NGS into the current laboratory setting for pathogen genomic surveillance can be hampered by the lack of resources and knowledge gap in the healthcare workforce. Strengthening the pathogen genomic surveillance by considering various factors such as sampling strategies, sequencing approaches, data analysis, storage and sharing, staff competency and maintenance of sequencing facilities is crucial to ensure the sustainability of a genomic surveillance program. The challenges and opportunities of implementing and integrating existing NGS technologies for pathogen genomic surveillance will be highlighted and discussed. The rapid expansion of the genomic surveillance program to other pathogens beyond SARS-CoV-2 is essential given the insights that can be derived from genomic data and to prepare for future pandemics.